geographic analysis A politician for the problems of the border cities between Iraq and its Arab surroundings - Aswad Salem, Nassif Jassim; Madin, Gah Ghanem (Journal of Tikrit University for Humanities, 2022)
The problem of demarcation of international borders is one of the problems of great interest in political geography as long as these problems and conflicts are a major cause of the outbreak of international disputes and crises and the outbreak of international conflicts. Accordingly, the rules and principles of international law are keen to find specific legal mechanisms in this framework. The countries accepted for a long time and recommended the conflicting countries to be guided or guided by their provisions in resolving or settling any border disputes between them. Whether these agreements were related to the demarcation of land, sea or river borders. These countries were convinced to enter into direct negotiations, for the purpose of concluding certain agreements or formulas of its own volition and choice without geopolitical and geo-economic effects on any of the parties. These agreements were based on the principle of equality and sovereignty enjoyed by all member states of the United Nations, either by resorting to the judiciary for the arbitration of the two states to resolve these disputes.The study embodies a problem with a spatial sense to show what is the role of natural and human geographical characteristics in demarcating the Iraqi border cities with the neighboring Arab countries? Do the world powers have a role in demarcating those Iraqi borders with the neighboring Arab countries? And then what are the effects that resulted from the demarcation of the Iraqi-Arab borders? Note that the geographical demarcation of the Iraqi borders with neighboring countries did not meet the desire of Iraq, as his view was not taken into account by the colonial countries represented by Britain after the First World War, and Iraq considered the demarcation of the borders in this way unfair to its right after deducting parts of it for the establishment of the State of Kuwait for its purposes. political changes, as well as the exploitation of the political changes that occur in Iraq by neighboring countries to choose the appropriate timing for drawing the borders, as happened during the Iran-Iraq war, where Jordan requested the demarcation of the borders with Iraq and actually drew the borders, and Jordan achieved geo-economic gains at the expense of Iraq, in addition to the latest amendment that took place on the the Iraqi-Saudi border with the division of the neutral zone between the two countries in 1981, according to the geopolitical perspective.